The impact of using concept maps in learning the skill of preparing volleyball players - Hakit, Ali (Journal of Physical Education, 2017)
The maps concepts are tool enable us to organization concedes in hierarchicalformat ranging in which the concepts by degree abstraction from its the most abstract toconcepts least abstraction thus stand out the relations between the concepts is increasing thelink and meaning among themselves, the problem find it is through the work of theresearcher as an assistant coach team volleyball in directorate rusafa second noted twice aclear relation to understand application. Skills volleyball demolition of their knowledge withits laws of lissome players the objective of search to the construction of education program in accordance with the strategy of maps concepts players squad raising rusafa second inBaghdad ball plane. have chosen the researcher curriculum pilots convenient to search thesample is made up than30 player distributors event the researcher concluded that learning atthe skill of preparation at the end of the learning period and the researcher recommended thatthe attention of volleyball coach to use the strategy of conceptual maps in the developmentof learning processes in the two sides of the application and theoretical.